Anatomical, Histological, Hormonal, And Ultrasonography Study Of Neonate Thyroid Gland - Anas Hamed Musleh; Abdul-Jabbar Jameel Al-Samarrae; Saad Ahmad Al-Rawi (Tikrit Journal of Pure Science, 2019)
Materials And Methods: The neonate thyroid gland collected and inspected grossly and taken all measurements. Then histologically preparation of the slides and stained with routine Haematoxylin and Eosin (H&E) and special stains for descriptive study. Alive healthy neonates was taken for assessment of thyroid stimulation hormone, in addition the volume by ultrasound and using ellipsoid formula 0.479 as correction factor.